(untitled) (Texas Journal of Philology, Culture and History, 2025)
This expanded article provides an in-depth exploration of innovative approaches to teaching the mother tongue—particularly the Uzbek language—within the framework of modern education. As global pedagogical paradigms shift toward learner autonomy, digital integration, and competency-based instruction, mother‑tongue education must adopt updated methodologies that correspond to the intellectual, technological, and cultural needs of 21st‑century learners. The article reviews theoretical foundations, interactive and digital instructional approaches, corpus-based learning, project methodologies, alternative assessment strategies, sociocultural considerations, and systemic challenges. Practical recommendations for teachers, administrators, and policymakers are provided